Intermolecular Photoredox Coupling: Alternative to Norrish Type II Reaction and Yang Cyclization in Ketones with γ‐C−H Bonds. Issue 26 (9th June 2021) - Hoffmann, Heiko; Tausch, Michael W.
Abstract: A new reaction pathway for the photoconversion of butyrophenone in acetonitrile was investigated. In addition to the classic intramolecular photoreactivity of ketones with γ‐C−H bonds (Norrish type II fragmentation and Yang cyclization), intermolecular generated species were isolated and characterized: 1, 2‐Dibenzoylethane, 2‐phenacylacetonitrile (oxidized species) and pinacols (reduced species). They account for approx. 20 % of the converted starting material, similar to the Yang product. The acetophenone enol intermediate, formed in situ via the Norrish type II reaction, has been identified as an H‐atom donor for the main intermolecular reaction steps, and has been distinguished from other conceivable mechanistic possibilities. Experimental results with analogue compounds suggest that the intermolecular product formation pathway may be of general relevance. Abstract : A new reaction pathway of the photoconversion of butyrophenone is reported. In addition to the Norrish type II fragmentation and Yang cyclization, intermolecular species are generated: 1, 2‐Dibenzoylethane, 2‐phenacylacetonitrile and pinacols. They account for approx. 20 % of the converted starting material, similar to the Yang product. The acetophenone enol intermediate has been identified as an H‐atom donor for the proposed mechanistic steps.